Two new species of the spider genus Songthela (Mesothelae, Liphistiidae) from Hunan Province, China - Shoushuo Han; Yan Zhang; Daiqin Li; Xin Xu (ZooKeys)
Two new species of the primitively segmented spider genus Songthela Ono, 2000, which were collected from Hunan Province, China, are described based on specimens of both sexes: S. dongta sp. nov. (♂♀), and S. lixi sp. nov. (♂♀). Songthela dongta sp. nov. is assigned to the bispina-group, while S. lixi sp. nov. belongs to the unispina-group, based on the morphology of male palps and female genitalia. We also provide mitochondrial cytochrome c oxidase subunit I (COI) sequences for species identification and calculate the intra- and interspecific genetic distance among these two new species and 26 known Songthela species. These molecular data highlight distinct genetic divergence between the two new species and their congeners, facilitating future species delimitation. This study not only expands the known diversity of Songthela, but also contributes to a growing framework for understanding biogeographic patterns and evolutionary processes in ancient spider lineages.